Government size and output volatility: New international evidence - Erkki Koskela; Matti Viren (The Research Institute of the Finnish Economy (ETLA), 2003)
This paper re-examines the relationship between government size and output volatility from two perspectives. First, we use a wider international data set of 91 countries over the period 1980-1999 and thus not only the OECD data that have thus far been utilized. Second, we also allow for time series aspect by using panel data estimations. We have two new findings. First, the results from OECD countries about the negative relationship between output volatility and government size cannot be generalized to a wider international data set. Second, the relationship between government size and output volatility seems to be non-linear. More precisely, the negative effect of government size on output volatility is significantly negative only for countries with high and small public sectors.
Keywords: E32; E62; H30; 330; automatic stabilizers; government size; output volatility; Staatsquote; Volatilität